Academic literacy: Plagiarism in pre-university students’ academic writing - Mah, F.; Ting, Su Hie (2013)
The study examined pre-university students’ awareness and practices of plagiarism. The specific aspects examined were (1) perceived necessity to include citations in assignments, (2) preferred penalties for plagiarism, and (3) academic writing practices.Analysis of questionnaire responses of 28 pre-university students in a private university showed that the students were aware of necessity to include citations but had inadequate knowledge of citation conventions. A majority of the students felt that plagiarism should be penalised but preferred resubmission of assignments rather than a fail in the course. The most common academic writing practice is patchwork plagiarism where students combine texts from different sources without proper citation and referencing. The findings suggest that the unintentional plagiarism resulting from lack of awareness on plagiarism needs to be addressed in pre-university education.